Effect of Workplace Environment on the Employees’ Performance in Nepalese Commercial Banks - K.C., Rohit; Sah, Puja (Nepalese Journal of Management, 2025)
This study examines the effect of workplace environment on the employees’ performance in Nepalese commercial banks. Employee’s performance is the dependable variable. The selected independent variables are work-life balance, supervisory support, organizational culture, work place incentives and physical work environment. The primary source of data is used to assess the opinions of the respondents regarding the effect of workplace environment on the employees’ performance in Nepalese commercial banks. The study is based on primary data of 179 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and different factors influencing effect of workplace environment on the employees’ performance in Nepalese commercial banks. The result shows that work-life balance has a positive impact on employee’s performance. It indicates that increase in work-life balance leads to increase in employee’s performance. Likewise, supervisory support has a positive impact on employee’s performance. It indicates that increase in supervisory support leads to increase in employee’s performance. Similarly, organizational culture has a positive impact on employee’s performance. It means that workplace incentives in the organization leads to increase in employee’s performance. Moreover, physical work environment has a positive impact on employee’s performance. It indicates better the physical work environment higher would-be employee’s performance.